Kemampuan Komunikasi Matematis Siswa SMP dalam Menyelesaikan Masalah Aritmetika Sosial Ditinjau dari Kemampuan Matematika Siswa - Fakhtiyah Nur Rosidah; Endah Budi Rahaju (Universitas Negeri Surabaya, 2026)
This study aimed to describe the mathematical communication skills of junior high school students with high, moderate, and low mathematical ability in solving social arithmetic problems. A qualitative approach was employed. The research subjects consisted of three Grade VII students of the same gender representing different levels of mathematical ability. The findings revealed differences in mathematical communication skills across levels of ability at each stage of problem solving. Students with high and moderate mathematical ability were able to identify relevant information, represent known data using mathematical symbols, and relate given information to previously learned concepts to determine appropriate strategies. However, only the high-ability student was able to formulate a clear strategy for solving the problem. The student with low mathematical ability experienced difficulties in identifying relevant information, using mathematical symbols, and determining appropriate strategies. At the implementation stage, students with high and moderate ability were able to apply mathematical symbols in executing problem-solving strategies, although they encountered difficulties in fully implementing their plans. Meanwhile, the low-ability student was unable to apply the planned strategies effectively. At the rechecking stage, students at all ability levels were unable to evaluate their solutions using alternative strategies.